2020
DOI: 10.1038/s41419-020-2667-x
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 inhibits breast cancer stem cells via c-Myc-mediated metabolic reprogramming

Abstract: Breast cancer stem cells (BCSCs) are considered to be the root of breast cancer occurrence and progression. However, the characteristics and regulatory mechanisms of BCSCs metabolism have been poorly revealed, which hinders the development of metabolism-targeted treatment strategies for BCSCs elimination. Herein, we demonstrated that the downregulation of Caveolin-1 (Cav-1) usually occurred in BCSCs and was associated with a metabolic switch from mitochondrial respiration to aerobic glycolysis. Meanwhile, Cav-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 48 publications
6
56
0
Order By: Relevance
“…In the present study, we further demonstrated that Cav-1 might act as the main pharmaceutical target of SA in suppressing metastasis on triple-negative breast cancer cell lines. This finding was also consistent with our previous study demonstrating that Cav-1 had higher expression in triple-negative breast cancer cell line MDA-MB-231 compared to other subtype cell lines ( Wang et al, 2020 ). Our pilot study also demonstrated that Cav-1 acts as the upstream regulator of NF-κB in breast cancer ( Jiao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, we further demonstrated that Cav-1 might act as the main pharmaceutical target of SA in suppressing metastasis on triple-negative breast cancer cell lines. This finding was also consistent with our previous study demonstrating that Cav-1 had higher expression in triple-negative breast cancer cell line MDA-MB-231 compared to other subtype cell lines ( Wang et al, 2020 ). Our pilot study also demonstrated that Cav-1 acts as the upstream regulator of NF-κB in breast cancer ( Jiao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 93%
“…E3 ligase SKP2, HUWE1, FBX29, TRUSS, RCHY1, CHIP, FBXW7, VHL, SPOP, TRIM32, NEDD4 and FBXL14 can target c-Myc for ubiquitination and degradation [149][150][151][152][153][154][155][156][157][158][159][160]. Decreased ubiquitination of c-Myc by VHL is observed to drive aerobic glycolysis in breast cancer cells [159]. Mutation or deletion of these E3 ligase genes induces carcinogenesis by attenuating c-Myc degradation.…”
Section: Ubiquitination Of C-mycmentioning
confidence: 99%
“…For example, cancer cells usually exhibit a metabolism switch characterized by decreased mitochondrial oxidative phosphorylation as well as elevated glycolysis, leading to the overproduction of toxic glucose metabolites. 161 The toxic glucose metabolites such as lactate, sorbitol, diacylglycerol (DAG), and methylglyoxal (MG) could further contribute to the development of advanced glycation end products (AGEs). On one hand, the formation of AGEs could impair the phagocytosis function of M1-like macrophages within the TME.…”
Section: Metabolic Signalingmentioning
confidence: 99%